2022
DOI: 10.1108/ijoes-05-2022-0117
|View full text |Cite
|
Sign up to set email alerts
|

Leadership integrity and employees’ success: role of ethical leadership, psychological capital, and psychological empowerment

Abstract: Purpose This study aims to investigate the effect of leadership integrity on employees’ success. In this regard, the mediating role of ethical leadership and the moderating role of psychological capital and psychological empowerment were considered as well. Design/methodology/approach This study is an applied research and a descriptive-correlation survey that used quantitative data. Data were collected from 302 employees of a large factory in Iran who was selected randomly. The research questionnaire consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 90 publications
1
17
0
Order By: Relevance
“…The results of the study indicated that the four dimensions of psychological empowerment, namely meaning, competence, self-determination, and impact, have a positive impact on sustainable performance in Egyptian travel agencies. These findings are consistent with prior research that has highlighted the importance of psychological empowerment in enhancing employee motivation, job satisfaction, and performance (Spreitzer, 1995;Terkamo-Moisio et al, 2022;Yazdanshenas & Mirzaei, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the study indicated that the four dimensions of psychological empowerment, namely meaning, competence, self-determination, and impact, have a positive impact on sustainable performance in Egyptian travel agencies. These findings are consistent with prior research that has highlighted the importance of psychological empowerment in enhancing employee motivation, job satisfaction, and performance (Spreitzer, 1995;Terkamo-Moisio et al, 2022;Yazdanshenas & Mirzaei, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…These conditions result in creating an atmosphere of confidence and respect between employees and their managers. Moreover, empowered employees contribute significantly to achieving competitive advantage because of their powerful interactions with customers, innovative solutions to problems, and new initiatives to develop work (Gautam and Ghimire, 2017;Terkamo-Moisio et al, 2022;Yazdanshenas and Mirzaei, 2022).…”
Section: Psychological Empowermentmentioning
confidence: 99%
“…Honesty and openness refer to the ability of nurse leaders to foster an environment in which each team member feels obligated to uphold the objective of keeping patients safe. Yashdanshenaz et al ( 2022) found a positive influence of integrity and ethical values of leaders on the success of the employees, as well as on their psychological gains; moreover, they found an indirect effect of the staff's perceptions about ethical leadership [25].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, it has been observed that high levels of integrity correspond to high levels of trust (Butler, 1999; Yazdanshenas and Mirzaei, 2023). Leaders perceived to have high levels of integrity (i.e.…”
Section: Theoretical Perspectives and Empirical Evidencementioning
confidence: 98%